(untitled) (International journal of artificial intelligence, 2026)
The article analyzes the issue of developing a spiritual worldview in students scientifically and theoretically based on modern pedagogical approaches, highlighting the main pedagogical factors influencing the formation of a spiritual worldview, in particular, the educational orientation of the educational content, the educational role of the teacher. It also emphasizes the mutual harmony of these factors in ensuring the moral, social and personal development of students based on national and universal values.